The Sex Factor: Epidemiology and Management of Chronic Obstructive Pulmonary Disease in British Columbia - Pat G Camp; Munaza Chaudhry; Howard Platt; Michael Roch; Jeremy Road; Donald Sin; Robert D Levy (Canadian Respiratory Journal)
BACKGROUND: The prevalence and mortality of chronic obstructive pulmonary disease (COPD) in women have been predicted to overtake that of men within the next decade. These predictions are based in part on data from surveys using self-reports of a COPD diagnosis. Whether these predictions have been realized is unknown.